Comparing migrant integration in Ireland and Northern Ireland - Frances McGinnity; James Laurence; Emily Cunniffe (The Economic and Social Research Institute (ESRI), 2023)
The increase in inward migration has been an important change in Ireland and Northern Ireland in recent decades. Migration can bring opportunities but also challenges. Integration not only allows immigrants to contribute to the economic, social, cultural, and political life of their host country, but is also important for social cohesion and inclusive growth. This report examines migrant integration in Ireland and Northern Ireland, using information from national and international surveys as well as a consultation event with migrants, their representative groups and other key stakeholders. Migrants are defined as those born outside their country of residence. The report compares the composition of the migrant population in Northern Ireland and Ireland. It considers migrant employment rates and the nature of jobs they hold, as well as migrant-origin young people's academic outcomes and wellbeing, compared to their native-origin peers. It also considers attitudes to migrants in both jurisdictions, and migrants' experience of the border in Ireland.
Keywords: 330; Migranten; Soziale Integration; Vergleich; Nordirland; Irland